2007
DOI: 10.1016/j.chembiol.2007.10.018
|View full text |Cite
|
Sign up to set email alerts
|

A Squalene Epoxidase Is Involved in Biosynthesis of Both the Antitumor Compound Clavaric Acid and Sterols in the Basidiomycete H. sublateritium

Abstract: The basidiomycete Hypholoma sublateritium produces the triterpenoid antitumor clavaric acid, an inhibitor of the human Ras-farnesyl transferase. The H. sublateritium squalene epoxidase gene (erg1) has been cloned and shown to encode a flavoprotein monooxygenase that requires FAD, NADPH, and P450 cofactors. Silencing of the erg1 gene in H. sublateritium using constructions expressed from the gdh promoter of Agaricus bisporus showed that the squalene epoxidase is involved in clavaric acid formation and in ergost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…Squalene epoxidase can carry out two successive epoxidations, performing the mirror image epoxidations of both the 2,3 and 22,23 end positions of the squalene molecule. Di-epoxidation of squalene by squalene epoxidase has been reported in numerous triterpenoid synthase systems (25)(26)(27)(28)(29), and plant squalene epoxidases have been functionally expressed and shown to yield both mono-and di-oxidosqualene (30,31). Modeling of the SgSQE protein supports di-epoxidation and indicates that the presence of the first epoxy oxygen does not hinder the docking for the second epoxidation (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Squalene epoxidase can carry out two successive epoxidations, performing the mirror image epoxidations of both the 2,3 and 22,23 end positions of the squalene molecule. Di-epoxidation of squalene by squalene epoxidase has been reported in numerous triterpenoid synthase systems (25)(26)(27)(28)(29), and plant squalene epoxidases have been functionally expressed and shown to yield both mono-and di-oxidosqualene (30,31). Modeling of the SgSQE protein supports di-epoxidation and indicates that the presence of the first epoxy oxygen does not hinder the docking for the second epoxidation (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 88%
“…It was shown that the cyclization outcome of this enzyme (as for diterpene synthases, see above) can be readily altered; substitution of one amino acid residue was sufficient to direct cyclization either towards lanosterol or protostadienol [224]. Two genes, oxidosqualene synthase and squalene epoxidase, were identified in the antitumor clavaric acid producer Hypholoma sublaterium (a basidiomycete), and are expected to be required for the production of this secondary metabolite [225,226]. In an effort to elucidate the biosynthesis of lanosterane-type triterpenoids in Wolfiporia and Ganoderma, genomic and transcriptomic studies were published by several groups [227][228][229][230].…”
Section: Fungal Triterpenoid Biosynthesismentioning
confidence: 99%
“…Then it was discovered in fungi as an enzyme taking part in ergosterol synthesis and in plants, where it is a part of phytosterols synthesis pathways (Petranyi et al , 1984 ;Godio et al , 2007 ;Rasbery et al , 2007 ;Uchida et al , 2007 ;He et al , 2008;Han et al , 2010 ). SE was also identifi ed in some bacteria which produce pentacyclic triterpens instead of sterols, so-called hopanoids synthesized from squalene by squalene-hopene cyclase (SHC) (EC 5.4.99.17) (Nakano et al, 2003;Pearson et al , 2003 ;Volkman , 2003 ;Nakano et al , 2007 ).…”
Section: Introduction: Squalene Monooxygenasementioning
confidence: 99%